Quantifier proof Question

  • Thread starter badwolf23
  • Start date
  • #1
1
0
Hello, I have no idea how to solve this proof and would actually appreciate your help. I cannot use soundness or completeness.

⊢ (∀x.ϕ) →(∃x.ϕ)


Thanks
 

Answers and Replies

  • #2
MLP
32
0
Hello, I have no idea how to solve this proof and would actually appreciate your help. I cannot use soundness or completeness.

⊢ (∀x.ϕ) →(∃x.ϕ)


Thanks
It will depend on the particular deductive apparatus. You might be using a set of axioms together with a set of rules of inference, or you might be using a system of natural deduction, etc. Let's suppose it's a natural deduction system.

Assume your antecedent. Often you will have a rule of universal instantiation that allows you to go from the assumed antecedent to an instance, then a rule that lets you go from the instance to the existential generalization of the instance (which is the consequent). Then an application of conditionalization gets you home. Does that help?
 
Last edited:

Related Threads on Quantifier proof Question

Replies
5
Views
416
  • Last Post
Replies
2
Views
544
  • Last Post
Replies
3
Views
619
Replies
10
Views
6K
  • Last Post
Replies
4
Views
1K
Replies
10
Views
243
  • Last Post
Replies
4
Views
1K
  • Last Post
Replies
1
Views
1K
  • Last Post
Replies
6
Views
2K
Replies
18
Views
1K
Top